To the Dialogo della pittura. Lodovico Dolce and his Lettere di diversi of 1554-1555 - Arroyo Esteban, Santiago (Anales de Historia del Arte, 2010)
Approach to the prehistory of the Dialogo della pittura by Lodovico Dolce (1557), paying special attention to its connection with the letters by Michelangelo, Raphael and Titian included in the Lettere di diversi (1554) compiled by the writter. In Appendix also the translation into Spanish and comment of the letters of artistic argument that appeared in the second edition of the Lettere (1555) which Dolce addressed to Gasparo Ballini and Alessandro Contarini.
Keywords: Lodovico Dolce; Lettere; Dialogo della pintura; Gasparo Ballini; Alessandro Contarini; Titian; Raphael; Michelangelo; Artistic literature; Art theory; Ut pictura poesis; Ékphrasis; Venus and Adonis; Variety; Invention; Design; Coloring